THE UPGRADING OF PETROLEUM RESIDUUM AND COAL IN CATALYTIC COPROCESSING - HWANG, J; KIM, H; LIM, GB; CURTIS, CW (KOREAN INST CHEM ENGINEERS, 1995)
The combined catalytic reactions using different types of petroleum residuum and coal were performed at 425 degrees C and 60 minutes in the presence of hydrogen to upgrade both materials to high quality synthetic fuels. In order to improve this coprocessing technology, the effect of the chemical and physical properties of both materials on the coprocessing product yields was investigated through a parametric study. In all reaction combinations, substantial increase in maltene production and high coal conversions of over 84% were observed regardless of petroleum residuum type and coal rank. The petroleum residuum properties of specific gravity and conradson carbon residue had effects on asphaltene production and coal conversion. The results of quantitative analysis for the amount of coal upgraded during coprocessing lead to conclude that a large amount of coal converted to maltene fraction due to high catalytic activity and reactive hydrogen donor richness of coprocessing system. However, most of the heavier fractions were formed primarily from coal regardless of the type of residuum used.